1987
DOI: 10.1111/j.1365-2265.1987.tb00805.x
|View full text |Cite
|
Sign up to set email alerts
|

Acromegaly

Abstract: SUMMARY A personal series of 256 cases of acromegaly/gigantism seen over a 20‐year period from 1963 is described. The insidious nature of the condition resulted in delay in diagnosis which was often made by a doctor when seeing the patient for an unrelated problem. Other features which commonly led to the diagnosis being made were headache, change in appearance, carpal tunnel syndrome, amenorrhoea and diabetes. The Hardy system for grading the radiological appearance of the pituitary tumour was used. Widely in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
306
5
16

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 500 publications
(358 citation statements)
references
References 78 publications
31
306
5
16
Order By: Relevance
“…(24) described thyroid cancer as the most common malignancy associated with acromegaly: the incidence rate of thyroid cancer was 5% for all patients, and 8% in patients who had a nodule in the thyroid gland. Balkany and Cushing (25) reported that thyroid tumors are predominantly papillary and occasionally aggressive, as confirmed by the rare occurrence of multifocal tumors and by low mortality rates (1,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(24) described thyroid cancer as the most common malignancy associated with acromegaly: the incidence rate of thyroid cancer was 5% for all patients, and 8% in patients who had a nodule in the thyroid gland. Balkany and Cushing (25) reported that thyroid tumors are predominantly papillary and occasionally aggressive, as confirmed by the rare occurrence of multifocal tumors and by low mortality rates (1,26).…”
Section: Discussionmentioning
confidence: 99%
“…A cromegaly is a chronic and multisystemic disease, with an estimated prevalence of 40-70 cases/million (1)(2). Chronic GH hypersecretion is caused by benign pituitary adenoma in most of the cases (3).…”
Section: Introductionmentioning
confidence: 99%
“…Adjustments for energy intake and other possible confounders such as body weight, socio-economic status, smoking and family history of the disease were not possible in all studies. Of the seven studies that did include these adjustments (Bostick et al, 1994;Macquart-Moulin et al, 1986,1987La Vecchia et al, 1993;Centonze et al, 1994;Slattery et al, 1997), six (Bostick et al, 1994;MacquartMoulin et al, 1987;La Vecchia et al, 1993;Centonze et al, 1994;Slattery et al, 1997) found a significant increase in risk of colorectal cancer with high sugar consumption, with odd ratios (ORs) ranging from 1.4 to 2.8 for the highest quartile or quintile of intake. The picture is further complicated when food groups were analysed.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Acromegaly increased the risk by four-fold (Nabarro, 1987) with a twofold increase in mortality from breast cancer (Orme et al, 1996). Also height has been directly associated with breast cancer (van den Brandt et al, 1997).…”
Section: Glycemic Index In Chronic Disease Ls Augustin Et Almentioning
confidence: 99%
“…Expression of the growth hormone gene in the mammary gland has also been demonstrated in humans and in cats (18,19). There appears to be a correlation between high plasma levels of growth hormone and the incidence of mammary tumours in humans (21). It is not clear yet whether growth hormone has direct effects on the promotion of mammary tumours.…”
Section: Discussionmentioning
confidence: 99%